Effect of thyroxin and cortisol on the hatching of eggs, larval morphometry and survival of Heteropneustes fossilis (Bloch) larvae - Nayak, P K; Mishra, T K; Ayyappan, S (Indian Journal of Fisheries, 2011)
Fertilized eggs of Indian catfish (Heteropneustes fossilis) were exogenously treated with L-thyroxin (T4; 0.05 mg/l), cortisol (0.5 mg/l) and cortisol + T4 (0.5 mg/l + 0.05 mg/l, respectively) by bath/immersion after three hours of fertilization up to 15 days of age to examine their effect on earlier development growth and survival of larvae. Growth and survival of larvae were significantly improved(P